Intravitreal injections at the Massachusetts Eye and Ear Infirmary: analysis of treatment indications and postinjection endophthalmitis rates. Issue 4 (6th February 2013) - Englander, Miriam; Chen, Teresa C; Paschalis, Eleftherios I; Miller, Joan W; Kim, Ivana K
Abstract : Aim: To report the incidence rate of acute postoperative endophthalmitis secondary to therapeutic intravitreal injections. Methods: A retrospective review of all consecutive eyes after intravitreal injections was performed at the Massachusetts Eye and Ear Infirmary, Boston, from 1 January 2007 to 31 December 2011. Results: During the 5-year study interval, 10 208 intravitreal injections were performed. The overall incidence rate of endophthalmitis was 0.029% per injection (3 of 10 208 injections). In the three cases, in our series, the endophthalmitis occurred at an average of seven injections, which lies within the SD of the mean number of injections received by each eye in this study, suggesting approximately equal probability of infection for each eye after receiving multiple, sequential injections. Bacterial cultures and Gram stain revealed coagulase-negative Staphylococcus species (n=1), moderate bacteria with negative culture (n=1) and moderate Staphylococcus epidermidis (n=1). All cases were successfully treated using either intravitreal antibiotics and steroids or pars plana vitrectomy. Best-corrected visual acuity reduction was not clinically significant at the last visit (>7 months for all cases). Conclusions: Acute endophthalmitis is a rare potential complication after intravitreal injection. Further studies are required to elucidate the best prophylactic and aseptic techniques to prevent this rare complication.